Reverse pharmacophore mapping and molecular docking studies for discovery of GTPase HRas as promising drug target for bis-pyrimidine derivatives - Kumar, Sanjiv (Chem Cent J, 2018)
BACKGROUND: Pyrimidine is an important pharmacophore in the field of medicinal chemistry and exhibit a broad spectrum of biological potentials. A study was carried out to identify the target protein of potent bis-pyrimidine derivatives using reverse docking program. PharmMapper, a robust online tool was used for identifying the target proteins based on reverse pharmacophore mapping. The murine macrophage (RAW 264.7) and human embryonic kidney (HEK-293) cancer cell line used for selectivity and safety study. METHODS: An open web server PharmMapper was used to identify the possible target of the developed compounds through reverse pharmacophore mapping. The results were analyzed and validated through docking with Schrodinger v9.6 using 10 protein GTPase HRas selected as possible target. The docking studies with Schrödinger validated the binding behavior of bis-pyrimidine compounds within GTP binding pocket. MTT and sulforhodamine assay were used as antiproliferative activity. RESULTS AND DISCUSSION: The protein was found one of the top scored targets of the compound 18, hence, the GTPase HRas protein was found crucial to be targeted for competing cancer. Toxicity study demonstrated the significant selectivity of most active compounds, 12, 16 and 18 showed negligible cell toxicity at their IC(50) concentration. CONCLUSION: From the results, we may conclude that GTPase HRas as a possible target of studied bis-pyrimidine derivatives where the retrieved information may be quite useful for rational drug designing. [Image: see text]